Hemispheric lateralization of semantic feature distinctiveness. (August 2015) - Reilly, M.; Machado, N.; Blumstein, S.E.
Abstract: Recent models of semantic memory propose that the semantic representation of concepts is based, in part, on a network of features. In this view, a feature that is distinctive for an object (a zebra has stripes) is processed differently from a feature that is shared across many objects (a zebra has four legs). The goal of this paper is to determine whether there are hemispheric differences in such processing. In a feature verification task, participants responded 'yes' or 'no' following concepts which were presented to a single visual field (left or right) paired with a shared or distinctive feature. Both hemispheres showed faster reaction times to shared features than to distinctive features, although right hemisphere responses were significantly slower overall and particularly in the processing of distinctive features. These findings support models of semantic processing in which the dominant left hemisphere more efficiently performs highly discriminating 'fine' encoding, in contrast to the right hemisphere which performs less discriminating 'coarse' encoding. Abstract : Highlights: Features are category-shared (a zebra has four legs) or distinctive (a zebra has stripes). We presented lateralized (L/R visual field) concept/feature pairs for verification. Shared features are processed more slowly than distinctive features. The right hemisphere was particularly slow to process distinctive features. We discuss implications for models of hemispheric lateralization and semantic memory.